The Importance of Natural Indigo Dye and Its Revitalization and Ethiopian Potential for Indigo Growing - Abera Kechi Kabish; Molla Tadesse Abate; Zelalem Adane Alemar; Solomon Girmay (Advances in Materials Science and Engineering)
The recent increasing consciousness for environment sustainability and health hazards is the motive for looking for alternative environment-friendly materials and manufacturing processes. Therefore, environmental compatibility and safety to the health manufacturing process are a worldwide concern. The use of excessive and toxic synthetic dyes in textile and apparel manufacturing processes lineages environment pollution and health hazards to the surroundings where they are sited. Consequently, penetrating for alternative eco-friendly dyes has been initiated in recent times by researchers and development motivators in order to reduce the excessive use of synthetic dyes. In this regard, natural indigo dye from the indigo plant is getting attention, and thus, it is preferred as good as synthetic indigo dye, owing to its inherited dyeing property. With natural indigo dye, it can be achieved eco-friendly dyeing without the application of mordant attaining commercially acceptable fastness properties. Owing to the popularity of blue jeans around the world, especially those that are naturally dyed indigo blue, indigo dye consumption is now rising. Furthermore, currently, natural indigo dye is demanding for functional textile finishing, cosmetics and food colouration, UV protection and deodorizing agents, and other applications. In general, because of its increasing demand and wide applications, natural indigo has become an important cash crop and is traded in the international market with a price range of 35 to 40 USD per kilogram as per its purity level. Indigo dye has therefore been revived with more applications than it had before the advent of man-made colourants. The revival of indigo presents a chance for underdeveloped nations with incorporated economic and social benefits. Ethiopia as a developing country and situated in tropical Africa will benefit from indigo revival because of its potentials with having a suitable climate, a young workforce, enough land resource, and its booming textile and apparel industries.